2009
DOI: 10.1103/physrevd.80.063525
|View full text |Cite
|
Sign up to set email alerts
|

Angular-planar CMB power spectrum

Abstract: Gaussianity and statistical isotropy of the universe are modern cosmology's minimal set of hypotheses. In this work we introduce a new statistical test to detect observational deviations from this minimal set. By dening the temperature correlation function over the whole celestial sphere, we are able to independently quantify both angular and planar dependence (modulations) of the CMB temperature power spectrum over dierent slices of this sphere. Given that planar dependence leads to further modulations of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…where the detailed form of the quantity on the right-hand side is model-dependent (see the more detailed discussions in [61][62][63]). There are many possibilities for how the absence of statistical isotropy might arise.…”
Section: E Cosmological Explanationsmentioning
confidence: 99%
“…where the detailed form of the quantity on the right-hand side is model-dependent (see the more detailed discussions in [61][62][63]). There are many possibilities for how the absence of statistical isotropy might arise.…”
Section: E Cosmological Explanationsmentioning
confidence: 99%
“…Several groups (de Oliveira-Costa et al 2004;Abramo et al 2006;Land & Magueijo 2007;Samal et al 2008;Rakić & Schwarz 2007) claim to have found a strong alignment between the preferred axes of the quadrupole and the octopole, which is commonly referred to as the axis of evil. Others (Bernui 2008;Eriksen et al 2007;Hoftuft et al 2009) have found a significant power asymmetry between the northern and southern ecliptic hemisphere, and some weaker anomalies have been found for the low multipoles beyond the octopole (Copi et al 2004;Land & Magueijo 2005;Abramo et al 2006;Pereira & Abramo 2009). However, the existence of such an isotropy breaking in the CMB temperature map is strongly under debate, and also negative results have been published (Souradeep et al 2006;Magueijo & Sorkin 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Here we are primarily interested in answering: how to detect planar signatures in CMB maps? One possibility was recently proposed in [56], where the two-point correlation function is decomposed in such a way as to account for the presence of symmetry planes in temperature maps. Given that CMB experiments are confined to collecting data from inside our galactic plane, it is conceivable that we may find planar signatures in the data if foregrounds were improperly removed.…”
Section: Jcap12(2009)013mentioning
confidence: 99%
“…In this work we employ the angular-planar power spectrum analysis introduced in [56] to search for planar signatures both in partial and full sky-coverage temperature maps, allowing for possible effects due to residual foreground contaminations. Our analysis may therefore help to shed some light in the origin of the reported anomalies and test the robustness of cleaned maps due to foreground contamination in a model-independent way.…”
Section: Jcap12(2009)013mentioning
confidence: 99%